Evaluation of kernel elongation ratio and aroma association in global popular aromatic rice cultivars in tropical environment - Faruq, G.; Khalid, Norzulaani; Jennifer, A.H.; Subha, B.; Zulqarnain, M.; Osman, M.; Nazia, A.M.; Zulqarnain, M.; Mohammad, O. (Academic Journals, 2010)
Aroma and cooked kernel elongation are the most important quality traits of aromatic rice, which differentiate the highly valued aromatic rice from the other rice types. Previous studies on genetic analysis have shown that genes/QTLs for these two traits are linked. In the present study, it tried to evaluate the expression of aroma, kernel elongation and their association in 55 fine rice genotypes in the tropical environment of Malaysia. Highest percentage of elongation ratio was observed in Genotype E2 followed by E11, Gharib, E6, E26, E34, E35, E36, E19, E20 and E27. Aroma was observed in 34 rice genotypes and 10 were identified as superior. They are E11, Sadri, Gharib, E7, Kasturi, Rambir Basmati, E21, E13, E24, and Rato Basmati. Positive correlation (r = 0.59, p <= 0.05)) was observed between aroma and kernel elongation in these selected 10 genotypes. Three of them had strong aroma (score 4) and there genotypes were E11, Sadri and Garib. We observed that the outstanding 10 genotypes for aroma and highest kernel elongation ratio are not the same except for two of the genotypes (Garib and E11). Aroma concentration was significantly different in highest kernel elongation ratio performance of 10 genotypes. Similar results were also observed in top 10 aroma performing genotypes and their kernel elongation ratio also varied among each other. In addition, out of 55 aromatic genotypes 17 did not have any aroma; comparatively low kernel elongation ratio was also observed in many of the genotypes. This investigation indicated that association of aroma and kernel elongation ratio can be highly influenced by tropical environment. However, since two genotypes (Garib and E11) perform their normal aromatic and Kernel elongation ratio and aromatic expression are even in tropical Malaysian Environment, It can be concluded that this expression might be as a result of the influence of dominant nature of some associated genes.